2022
DOI: 10.3390/ijms23158636
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-Mediated Targeted DNA Integration: Rearrangements at the Junction of Plant and Plasmid DNA

Abstract: Targeted DNA integration into known locations in the genome has potential advantages over the random insertional events typically achieved using conventional means of genetic modification. We studied the presence and extent of DNA rearrangements at the junction of plant and transgenic DNA in five lines of Arabidopsis thaliana suspension cells carrying a site-specific integration of target genes. Two types of templates were used to obtain knock-ins, differing in the presence or absence of flanking DNA homologou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…The integration occurs according to the NHEJ or HDR mechanism, depending on the presence of homology regions surrounding the inserted DNA. Both mechanisms can lead to mutations and rearrangements at the ends of the inserted DNA region [110]. Moreover, while in experiments on animal cells, there are examples of highly efficient integration through the NHEJ mechanism [111], in the case of plants, the efficiency of integration through this mechanism is usually not so high [112].…”
Section: Features Of the Integration Of Foreign Genes Into The Plant ...mentioning
confidence: 99%
“…The integration occurs according to the NHEJ or HDR mechanism, depending on the presence of homology regions surrounding the inserted DNA. Both mechanisms can lead to mutations and rearrangements at the ends of the inserted DNA region [110]. Moreover, while in experiments on animal cells, there are examples of highly efficient integration through the NHEJ mechanism [111], in the case of plants, the efficiency of integration through this mechanism is usually not so high [112].…”
Section: Features Of the Integration Of Foreign Genes Into The Plant ...mentioning
confidence: 99%
“…While CRISPR/Cas9-targeted mutagenesis have been used in many plants, including legumes ( Table 1 ), HR-mediated targeted insertion remains a big challenge. This is probably because it operates only at the S and G2 phases of the cell cycle 20 , 28 , 29 , but also due to the difficulty of delivering template DNAs to plant cells surrounded by semirigid cell walls. Nonetheless, successful examples of HR (gene targeting) in different crop species have been achieved 6 , 30 .…”
Section: Limitations and Requirements For Efficient Crop Genome Editingmentioning
confidence: 99%
“…HR is a high-fidelity repair pathway that occurs mainly during the S and G2 phases of the cell cycle and often viewed as a high-fidelity pathway [50,51]. However, some studies also indicated that HR caused structural variation such as deletions and duplications [52,53]. NHEJ repair is an error-prone repair pathway that does not depend on the homologous template, and its repair process is not restricted to a certain stage of the cell cycle, often introducing small insertions and deletions in the genome [54,55].…”
Section: Synergistic Effects Of Multiple Dna Repair Pathways Are Indu...mentioning
confidence: 99%